Diagnostic and therapeutic recommendations for chronic pancreatitis. Recommendations of the Working Group of the Polish Society of Gastroenterology and the Polish Pancreas Club - Roland Kadaj-Lipka; Michał Lipiński; Krystian Adrych; Marek Durlik; Anita Gąsiorowska; Mirosław Jarosz; Grażyna Jurkowska; Ewa Małecka-Panas; Grzegorz Oracz; Mariusz Rosołowski; Barbara Skrzydło-Radomańska; Renata Talar-Wojnarowska; et al. (Gastroenterology Review)
This article describes the latest diagnostic and therapeutic recommendations in chronic pancreatitis, developed by the Working Group of the Polish Society of Gastroenterology and the Polish Pancreas Club. The recommendations refer to the diagnosis of chronic pancreatitis, autoimmune pancreatitis, conservative management, treatment of pain, and exocrine and endocrine pancreatic insufficiency, treatment of chronic pancreatitis by endoscopic and surgical methods, and oncological surveillance of chronic pancreatitis. This paper refers to the Polish recommendations published in 2011, which have been updated and supplemented. All recommendations were voted by experts of the Polish Society of Gastroenterology and the Polish Pancreas Club, who evaluated them each time on a five‑degree scale, where I meant full acceptance, II – acceptance with some reservation, III – acceptance with serious reservation, IV – rejection with some reservation and V – full rejection. The results of the voting, together with a brief commentary, have been included with each recommendation put to the vote. In addition, the expert group assessed the value of clinical studies on which the statements are based, on a scale where A means high (based on meta‑analyses and randomised clinical trials), B means medium (based on clinical trials and observational studies), and C means low (based mainly on expert opinion).